Análise exergética com proposta de parâmetros de sustentabilidade energética e ambiental da fornalha da caldeira de recuperação Kraft de obtenção de celulose - Marcos Henrique Duarte Abreu (2023)
The Kraft process for cellulose extraction is characterized as a sector of significant investment in Brazil, providing substantial financial returns to the Brazilian economy. The Kraft process can be divided into two parts. The first part involves preparing wood chips to be cooked in a digester, separating lignin from cellulose fibers in the presence of white liquor. The result is cellulose pulp, with black liquor generated as a byproduct. The second part of the Kraft process involves the recovery stage, which reclaims compounds from the black liquor, returning them to the production cycle to form white liquor. The recovery stage is notable for the recovery boiler, which, by burning the black liquor, enables the production of a substantial amount of electrical energy. Due to environmental concerns regarding the use of renewable energy sources, such as black liquor, and the significance of the resulting electrical energy generation for the Kraft process, this study aims to propose energetic and exergetic analyses and the establishment of parameters to assess the efficiency and sustainability of the recovery boiler furnace. The proposed methodology is built upon existing studies in the literature. The description of the furnace's chemical composition is achieved using the Gibbs Energy Minimization technique. With the aid of an energy balance, it's possible to estimate the furnace and combustion gas temperatures. Industrial data and information available in the literature are used to validate the model's results, enabling the exergetic analysis and proposing efficiency and environmental impact parameters. The obtained results demonstrate that both chemical and physical exergy make significant contributions to the process. The exergetic efficiency of the furnace was 81%. However, a new efficiency proposal shows a result of 58% when considering the exergy wasted by the process.